Molecular phylogeny and morphology reveal a new species of Asterostroma from Guizhou Province, China - Zhou, Hong-Min; Gu, Zi-Rui; Zhao, Chang-Lin (Phytotaxa, 2024)
A new corticioid fungus from Guizhou Province in southwest China, Asterostroma rhizomorpharum, is described and illustrated based on morphological and molecular evidence. It is characterized by producing annual, resupinate basidiomata with long rhizomorphs, a dimitic hyphal structure with simple septa on generative hyphae, asterosetae frequently present in subiculum, asterohyphidia present in hymenium, ellipsoid to subglobose, and echinulate and amyloid basidiospores (5.5–6.8 × 4.6–5.9 μm). The phylogenetic analysis based on ITS+nLSU rDNA sequences shows that the new species belongs to the section Asterostroma.